Hide text in audio channels within files - Hassan AL-Numa (College of Education for Pure Sciences, 2018)
The aim of research and studies in the field of steganography to hide data inside other data are not aware, as the world witnessed during the recent period significant development in this area, and that the goal of this research is to hide the text data in secret within the media audio (wav), also been working on concealment within the channel audio in the video, and through access to the audio channels for each frame of video frames and include the data inside. When we hide in the channel audio video clip of the type (Avi), all within a framework of frameworks The video has audio channels belonging to him can been forced in any one of the audio channels for each frame of frames the video, so it is very hard to detect sites of concealment where the view of the capacity high for the video, it is possible to hide a very large amount of information without a clear change in the video, where the results of concealment in audio channel of digital video is fully compatible with the goal of the research.